Ataxia-telangiectasia in China: a case report of a novel ATM variant and literature review - Shao, Li; Wang, Haoyi; Xu, Jianbo; Qi, Ming; Yu, Zhaonan; Zhang, Jing (Frontiers in Neurology, 2023)
Background: Ataxia-telangiectasia (A-T) is a multisystem genetic disorder involving ataxia, oculocutaneous telangiectasia and immunodeficiency, caused by biallelic pathogenic variants in the ATM gene. To date most of ATM variants have been reported in Caucasian population, and few studies have focused on the genotype-phenotype correlation of A-T in Chinese population. We herein present a Chinese patient with A-T who carries compound heterozygous variants in the ATM gene, and conducted a literature review for A-T in China. Case presentation: A 7-year-old Chinese girl presented with growth retardation, ataxia, medium ocular telangiectasia, cerebellar atrophy and elevated serum alpha-fetoprotein (AFP) level, which supported the suspicion of A-T. Notably, the serum levels of immunoglobulins were all normal, ruling out the immunodeficiency. Exome sequencing and Sanger sequencing revealed two likely pathogenic ATM variants, Jinhua Maternal&Child Health Care Hospita 删除[吾真]: l 删除[吾真]: , 删除[吾真]: , which is 删除[吾真]:NM_000051.4: c.4195dup (p.Thr1399Asnfs*15) and c.6006+1G>T (p.?), which were inherited from the father and mother, respectively. From the Chinese literature review, we found that there was a marked delay in diagnosis of A-T and 38.9% (7/18) of A-T patients did not suffer from immunodeficiency in China. No genotype-phenotype correlation was observed in this group of A-T patients.Conclusion: These results extend the genotype spectrum of A-T in Chinese population and imply that the diagnosis of A-T in China should be improved.